The Great Bustard: Past, Present and Future of a Globally Threatened Species - Alonso Juan Carlos (Sciendo, 2014)
Great Bustards are still vulnerable to agricultural intensification, power line collision, and other human-induced landscape changes. Their world population is estimated to be between44,000 and 57,000 individuals, showing a stable demographic trend at present in the Iberian peninsula, its mainstronghold, but uncertain trends in Russia and China, and alarming declines in Iran and Morocco, where it willgo extinct if urgent protection measures are not taken immediately. Our knowledge of the behaviour and ecologyof this species has increased considerably over the last three decades, allowing us to control the major threatsand secure its conservation in an appropriately managed cereal farmland. This species became 'The Bird of the Year' in Hungary in 2014.